Cortactin function in invadopodia. (3rd July 2020) - Jeannot, Pauline; Besson, Arnaud
ABSTRACT: Actin remodeling plays an essential role in diverse cellular processes such as cell motility, vesicle trafficking or cytokinesis. The scaffold protein and actin nucleation promoting factor Cortactin is present in virtually all actin-based structures, participating in the formation of branched actin networks. It has been involved in the control of endocytosis, and vesicle trafficking, axon guidance and organization, as well as adhesion, migration and invasion. To migrate and invade through three-dimensional environments, cells have developed specialized actin-based structures called invadosomes, a generic term to designate invadopodia and podosomes. Cortactin has emerged as a critical regulator of invadosome formation, function and disassembly. Underscoring this role, Cortactin is frequently overexpressed in several types of invasive cancers. Herein we will review the roles played by Cortactin in these specific invasive structures.